Psycho-Oncological Intervention Through Counseling in Patients With Differentiated Thyroid Cancer in Treatment With Radioiodine (COUNTHY, NCT05054634): A Non-randomized Controlled Study - Javaloyes, Nuria; Crespo, Aurora; Redal, M. Carmen; Brugarolas, Antonio; Botella, Lara; Escudero-Ortiz, Vanesa; Sureda, Manuel (Frontiers in Psychology, 2022)
Background. Diagnosis and treatment of differentiated thyroid carcinomas cause anxiety and depression. Additionally, these patients suffer hormonal alterations, associated with psychological symptoms (changes in mood, emotional instability, memory loss, etc.). This study aims to evaluate the effectiveness of a psycho-oncological intervention based on Counselling to reduce anxiety and depression related with the treatment in patients with differentiated thyroid carcinomas. Methods. A non-randomized controlled study, with two groups (experimental, n=37, and control, n=38) and baseline and post-treatment measures was designed. Patients in experimental group received a psycho-oncological intervention based on Counselling in addition to the standard treatment. The independent variable was the assigned group and the dependent one was the evolution of anxiety and depression, analyzed separately, both evaluated using HADS. Other relevant covariables related with quality of life were also analyzed using SF-36 and PGWBI scales. Results. The difference of the post-treatment-baseline variation showed a statistically significant reduction in anxiety and depression in the experimental group in relation to the control group (p<0.001). The mean of PGWBI score increased significantly in the experimental group (p<0.001) and in the control group decreased significantly (p<0.001). All the baseline and the post-treatment scores of the variables evaluated showed a statistically significant improvement in the experimental group versus the control group. Conclusions. This study demonstrates significant benefits of psycho-oncological intervention based on Counselling in anxiety, depression, quality of life and well-being of the patient with differentiated thyroid carcinomas. Further studies are warranted.